Robot-assisted radical prostatectomy with da Vinci single-port system - Marek Kurowski; Karolina Kuczapska; Anna Gliwa; Monika Ryglewicz; Dariusz Fabian; Elżbieta Leszczyńska-Knaga; Natalia Jakubczyk; Weronika Rutkowska-Kawalec; Paweł Moczydłowski; Karolina Michalczuk (Journal of Education, Health and Sport)
Introduction and purpose